Analysis of Social Media Marketing Activity on Brand Awareness, Brand Image, and Brand Loyalty in Local Fashion Product Brands - Citra Adiningtyas; Yulia Nur Hasanah (Almana : Jurnal Manajemen dan Bisnis, 2023)
The development of technology makes social media a platform that is widely used by business people as a medium to sell or just become a promotional media due to its ease in reaching a wider consumer. This research aims to find out the influence of social media marketing activities based on the dimensions of entertainment, interaction, trendiness, customization, and electronic word of mouth on brand awareness, brand image, and brand loyalty through Instagram social media. The research uses quantitative methods and descriptive types of research. The study was conducted on people who follow the local fashion product brand on their Instagram accounts and have bought the products. The number of samples used is 400 people with a convenience sampling method. All data collected meets the criteria for validity and reliability. All data processing is done by using SPSS software version 26. The data were analyzed using multiple linear regression tests. This research showed that social media marketing activities based on five dimensions, entertainment, interaction, trendiness, customization, and word of mouth, have a significant effect on variables dependent on brand awareness, brand image, and brand loyalty.